FUZZY DELPHI METHOD FOR DESIGNING AND DEVELOPING ACID BASE Et-PBL MODULE TO IMPROVE PROBLEM-SOLVING SKILLS - Khaira, Kuntum; Ibrahim, Mohd Mokhzani (Chimica Didactica Acta, 2024)
Innovative and creative techniques and materials for teaching and learning are required to stay up with the advancements of globalization. The purpose of this study is to reach expert consensus on the precise and relevant components that should be used while designing and developing an acid-base Et-PBL module to improve problem-solving skills.This study's design is quantitative and employs the Fuzzy Delphi method.Thirty-three items made up the questionnaire instrument used to gather research data. Twelve experts from 10 different colleges who specialize in chemistry education and Islamic education participated in the study.Based on the expert consensus value over 75%, the fuzzy score (A) - cut value = 0.5, and the threshold value (d) 0.2, the data analysis results indicated that the experts accepted all these items. Consequently, it demonstrates that these components have been agreed upon by experts and are required for the design and development of the acid-based Et-PBL module